Pengaruh Kepercayaan, Persepsi Harga, dan Ulasan Produk Terhadap Minat Beli Ulang Produk Zoya di Outlet Kediri - Eria Suci Aningtyas; Supriyono Supriyono (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Online shopping can make it easier for people to get the things they want quickly and easily. It can also be done from anywhere. This study aims to discover how to trust, how people see prices, and how product reviews affect people's plans to repurchase Zoya products at Kediri Outlets. Quantitative research methods are used to do this. The sample used comprises 80 people who answered the survey questions. A Google form questionnaire was used to collect the information. PLS (Partial Least Square) software was used to analyze the data. The results of this study show that trust, how people see prices, and product reviews all positively and significantly affect the desire to buy again.